Effect of Single and Combined Cu, Nacl and Water Stresses on Three Atriplex Species with Phytostabilization Potential - Ortiz-Calderon, C (Elsevier B.V., 2020)
Phytostabilization of metal enriched substrates in arid and semiarid areas depends on the use of metal-tolerant or metallophyte plants in order to decrease metal mobilization and dispersion. However, the co-occurrence of other abiotic restrictions on plant growth, such as drought and salinity calls for a new perspective for plant selection. Since components of salt and drought tolerance traits of halophytes are also present in metal stress, Atriplex species, typical of dry and salty soils, emerge as good candidates for phytostabilization. But in order to confirm this potential, it is necessary to explore specific responses to increasing copper, salt and water stress. In this study, we compared the effect of single and combined copper, NaCl and PEG- induced water stresses on growth parameters of the Chilean Atriplex atacamensis, European A. halimus and Australian A. nummularia under controlled hydroponic assays. Results showed that increasing copper had severe effects on root development of all three species, with subsequent effects on their shoot biomass. Salt stress effects were mostly osmotic, with a decrease in shoot fresh weight and water content, and PEG- induced water stress had no clear effect on growth of roots and shoots. Combination of copper with NaCl and PEG further decreased plant growth, but this effect varied among Atriplex species. This shows that growth of Atriplex species responds differently to each individual stress and that stressor combination causes an overall negative effects in their growth parameters. © 2020 SAAB
Keywords: Halophyte; Metal enrichment; Phytotoxicity; Saltbush; Stressor